Studi Analisis Manajemen Risiko Pembiayaan Mudharabah di BMT Sidogiri Cabang Bondowoso - Ubaidillah, Ubaidillah (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Sekolah Tinggi Islam Blambangan (STIB) Banyuwangi, 2018)
In familiar Islamic financial institutions we hear the term mudharabah, mudharabah is a contract that involves between two or more people, namely the owner of investor capital (Shahibul Maal) who entrusts his capital to people (mudharib) to be managed. The division of mudaraba is divided into two, namely: the first: Mudharabah muqayyadah which means shahibul maal gives a limit to the funds invested. And secondly: Mudharabah Muthlaqah Shahibul Maal does not provide limits on the funds invested. The focus of this study is first how the implementation of mudharabah financing at BMT Sidogiri Branch Bondowoso. Second, what is the risk management strategy of mudharabah financing at BMT Sidogiri Branch Bondowoso. The research objectives are 1). To obtain information about the implementation of mudharabah financing at BMT Sidogiri Branch Bondowoso. 2). Want to describe the risk management strategy for mudharabah financing at BMT Sidogiri Branch Bondowoso. In this study the authors used qualitative research with interview methods, observation methods and documentation methods. so in the form of analysis we use qualitative descriptive analysis. The results showed that mudharabah financing at BMT Sidogiri Branch Bondowoso was in accordance with the Shari'a contained in sharia economic theory because in it the terms and conditions were met, but in mudharabah financing at BMT Sidogiri, Bondowoso Branch could only be realized in the form of fund collection